Signal Processing by Generalized Receiver in DS-CDMA Wireless Communication Systems with Optimal Combining and Partial Cancellation. (28th February 2011) - Tuzlukov, Vyacheslav
Abstract : Symbol error rate (SER) of quadrature subbranch hybrid selection/maximal-ratio combining (HS/MRC) scheme for 1-D modulations in Rayleigh fading under employment of the generalized receiver (GR), which is constructed based on the generalized approach to signal processing (GASP) in noise, is investigated.N diversity input branches are split into2 N in-phase and quadrature subbranches.M -ary pulse amplitude modulation, including coherent binary phase-shift keying (BPSK), with quadrature subbranch HS/MRC is investigated. GR SER performance for quadrature HS/MRC and HS/MRC schemes is investigated and compared with the conventional HS/MRC receiver. Comparison shows that the GR with quadrature subbranch HS/MRC and HS/MRC schemes outperforms the traditional HS/MRC receiver. Procedure of partial cancellation factor (PCF) selection for the first stage of hard-decision partial parallel interference cancellation (PPIC) using GR employed by direct-sequence code-division multiple access (DS-CDMA) systems under multipath fading channel in the case of periodic code scenario is proposed. Optimal PCF range is derived based on Price's theorem. Simulation confirms that the bit error rate (BER) performance is very close to potentially achieved one and surpasses the BER performance of real PCF for DS-CDMA systems discussed in the literature.